THE EFFECT OF TECHNOLOGY-ENHANCED LEARNING APPROACH ON EFL LEARNERS’ LISTENING SKILL: Received: 14th September 2021; Revised: 13th January 2022, 31st January 2022; Accepted: 02nd February 2022 - Lanping, Fu (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Listening skills, as one of the four macro skills in language teaching, is regarded as the most difficult one by some educators. This meta-analysis, computing the data from 20 previous studies, aims at studying the effect of a technology-enhanced learning approach on English learners’ listening comprehension. It also studied the difference between the effect of different treatment types and treatment length. Data shows that the technology-enhanced learning approach help learners improve more than the traditional learning approach, CALL works better than MALL and long-term treatment have greater effect than short term one, which suggests the application of suitable learning aid as well as a longer application.